Oceanic Mesoscale Cyclones Cluster Surface Lagrangian Material. Issue 4 (16th February 2022) - Vic, Clément; Hascoët, Solenne; Gula, Jonathan; Huck, Thierry; Maes, Christophe
Abstract: An asymmetry in the clustering of oceanic surface material has been observed at the submesoscales. Energetic and ephemeral submesoscale cyclonic fronts are associated with convergence zones, hence cluster surface material. Their anticyclonic counterparts do not feature such an effect. Yet, at the mesoscale, literature has been contradictory about such an asymmetry. Here, we combine surface drifter trajectories with an altimetry‐derived mesoscale eddy database in the North Atlantic to show that mesoscale cyclones contain 24% more drifters than anticyclones. A numerical Lagrangian experiment using a mesoscale‐resolving model quantitatively reproduces the observational results. It reveals that particles preferentially cluster in cyclonic regions, both in fronts and eddies. The model further suggests that ageostrophic cyclonic fronts concentrate particles a few days before the eddy formation and detection. Plain Language Summary: Earth's oceans are filled with swirling coherent structures called eddies, whose dominant scales range from 10 to 100 km across. Clockwise‐rotating and counter‐clockwise‐rotating eddies, called anticyclones and cyclones in the northern hemisphere, coexist in the oceans with similar proportions and covered areas. Dominant theories for the life cycle of the largest eddies (mesoscale eddies) have concurred on their kinematic symmetry. However, this symmetry breaks down at the small scales (submesoscale eddies and fronts) and cyclonic structures have been shown to be associated with convergence zones. Here, we combined a surface drifter database with a satellite‐derived mesoscale eddy database to show that mesoscale cyclones contain significantly more drifters than anticyclones. The use of a numerical Lagrangian experiment, that is, flow‐following inert particles, unveiled that the clustering of particles occurs in the formation stage of the cyclones. This work has implications for our global understanding of the transport of surface material in the oceans, for example, debris and plastics. Key Points: Surface Velocity Program drifters are preferentially trapped into mesoscale cyclones rather than in anticyclones Lagrangian analysis of a mesoscale‐resolving simulation shows that particles cluster preferentially in cyclonic fronts and eddies Particles cluster in cyclonic regions a few days before the formation and detection of mesoscale cyclones